Zinc complexes coordinated by bipyridine-phenolate ligands as an efficient initiator for ring-opening polymerization of cyclic esters. (15th January 2015) - Hsieh, Yi-Liang; Lin, Yi-Chien; Lee, Gene-Hsiang; Peng, Chi-How
Abstract: A series of zinc complexes coordinated by different bipyridine-phenolate (BpyPh ) ligands, 2-([2, 2′-bipyridin]-6-yl)-4, 6-di-tert-butylphenol (BpyPh 2, 4-tBu -H, 3 ) and 2-([2, 2′-bipyridin]-6-yl)-4-(tert-butyl)phenol (BpyPh 4-tBu -H, 4 ) have been synthesized. The reaction ofBpyPh 2, 4-tBu -H with ZnEt2 gave a six-coordinated complex of [(BpyPh 2, 4-tBu )2 Zn] (5 ) with the distorted octahedral geometry. However, the dinuclear complexes of [(BpyPh)Zn(μ-OBn)]2 (6 and7 ) were formed when benzyl alcohol was added and then can be converted to mononuclear zinc benzylalkoxide species by the increased temperature. The ε-CL and L-LA polymerizations initiated by complex6 showed the living characteristics of narrow molecular weight distribution (PDIs < 1.15) and the capability of block copolymer synthesis demonstrated by the formation of PCL- b -PVL and PCL- b -PHB. The ring-opening polymerizations of cyclic esters initiated by complex5, however, was not effective possibly due to the highly steric hindered metal center. Graphical abstract: Highlights: Designed ligands were obtained via a simple, one-pot synthetic process. Well controlled ring-opening polymerization of various cyclic esters was achieved. Different block copolymers of lactones have been synthesized.